2017
DOI: 10.3130/jaabe.16.115
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based Planning Model for Table Formwork Operation in Tall Building Construction

Abstract: Operation planning for table formwork using a crane-independent lifting system (CLS) is a crucial factor affecting productivity for formwork in tall building construction. Inappropriate heuristic operation plans are likely to increase work duration because of temporarily displaced stacks of table forms, and may also increase costs because of excessive use of equipment. The authors propose a simulation-based operation planning model for table formwork for efficient operations in tall building construction. By o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, all of these formworks have certain limitations and shortcomings [8,9]. Traditional bamboo and wood formworks have the advantages of light weight, easy processing, and low cost per layer, but the formwork quality is poor, and the service life is short [10][11][12]. The surfaces of plastic formworks are smooth, have good waterproof ability, are easy to demold, and are more convenient to process, manufacture, and recycle, but plastic formworks readily age and warp, and white waste easily forms after disposal, causing serious pollution to the environment [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, all of these formworks have certain limitations and shortcomings [8,9]. Traditional bamboo and wood formworks have the advantages of light weight, easy processing, and low cost per layer, but the formwork quality is poor, and the service life is short [10][11][12]. The surfaces of plastic formworks are smooth, have good waterproof ability, are easy to demold, and are more convenient to process, manufacture, and recycle, but plastic formworks readily age and warp, and white waste easily forms after disposal, causing serious pollution to the environment [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high investment cost (Vivek, 2016) and the environmental problems caused by the heavy usage of releasing agents to ease the stripping work of concrete means that there is a need to develop a new system form (Kim et al, 2010). Several existing studies suggested formwork planning model (Lim et al, 2017) and the equipment-centric formwork method (Kim et al, 2012) to solve such problems. These studies confirmed that formwork productivity can be improved by using the suggested planning model and new formwork method.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have aimed to evaluate the productivity of the table formwork method [1], supplement the element technologies [2], and automate the layout and operation plans for table forms [3,4]. Even though these studies increased the completeness of the table formwork method, improving work efficiency, they failed to understand the problems arising from the actual table form construction process, and could not propose improvement directions.…”
Section: Introductionmentioning
confidence: 99%